HBM4EU Chromates Study - Genotoxicity and Oxidative Stress Biomarkers in Workers Exposed to Hexavalent Chromium - Tavares, Ana (2022)
A study was conducted within the European Human Biomonitoring Initiative (HBM4EU) to characterize occupational exposure to Cr(VI). Herein we present the results of biomarkers of genotoxicity and oxidative stress, including micronucleus analysis in lymphocytes and reticulocytes, the comet assay in whole blood, and malondialdehyde and 8-oxo-2'-deoxyguanosine in urine. Workers from several Cr(VI)-related industrial activities and controls from industrial (within company) and non-industrial (outwith company) environments were included. The significantly increased genotoxicity (p = 0.03 for MN in lymphocytes and reticulocytes; p < 0.001 for comet assay data) and oxidative stress levels (p = 0.007 and p < 0.001 for MDA and 8-OHdG levels in pre-shift urine samples, respectively) that were detected in the exposed workers over the outwith company controls suggest that Cr(VI) exposure might still represent a health risk, particularly, for chrome painters and electrolytic bath platers, despite the low Cr exposure. The within-company controls displayed DNA and chromosomal damage levels that were comparable to those of the exposed group, highlighting the relevance of considering all industry workers as potentially exposed. The use of effect biomarkers proved their capacity to detect the early biological effects from low Cr(VI) exposure, and to contribute to identifying subgroups that are at higher risk. Overall, this study reinforces the need for further re-evaluation of the occupational exposure limit and better application of protection measures. However, it also raised some additional questions and unexplained inconsistencies that need follow-up studies to be clarified.